Knowledge Map : Content and Curriculum Issues - World Bank (Washington, DC, 2012)
At first glance, content issues related to information and communication technologies (ICTs) use in education might seem to some to be of minor importance. After all, access to the internet means access to an entire world of educational resources. Access to the internet provides access to seemingly endless sets of educational resources and indeed it does. However, experience shows that there is a dearth of educational resources in a format that makes them easily accessible and relevant to most teachers and learners in least development countries (LDCs), especially as they relate to a given country's current curriculum. Experience tells us that, unless electronic educational resources are directly related to the curriculum, and to the assessment methods used to evaluate educational outcomes (especially standardized testing), lack of appropriate and relevant educational content is actually an important barrier to ICT use in schools.